(3TQM GdJMQjQs - (3CHh GdMSf RjO Hf eMeOs; (3CHh WGdH jMji Hf GdMSjf Hf GdbGSe Hf gGQhf Hf CHj YjSi Hf Ydj GdgGQhfj,J (B424 (3g` s
(3ChdgG (B:s
(3cJGH COH GdbGVi , HGH UaGJ GdbGVi GdJi jLhR eYgG bVGDg eSCdg (B: (3HSe Gddg GdQMef GdQMje jLH Cf jchf GdbGVi YGdekG s
(3BNQgG (B:s
(3bGd Ydi GHf GdYHGS Yf CejQ GdeDefjf QVi Gdgd Yfg Gfg fgi Cgd GdPeI (B( (3ef (B) (3VQH GdfhGbjS ai CeUGQ GdeSdejf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B8 - (3U (B141s
(3JHUQGJ GdCUd (B:s
(3MGdI GdfSNI SjFI s
(3GdfSNI HgG JdhjK , CQVg s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds